2017
DOI: 10.21786/bbrc/10.1/20
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of controlling water coning in oil reservoirs through drilling of horizontal wells

Abstract: Oil production is affected by the reservoir pressure, where the higher the reservoir pressure, the higher the production rate. In most cases, water is also produced with oil, which can cause several negative issues. In oil wells, after a short period of oil production, early water production will cause serious decrease in oil production. Actually water coning is an event in which water and oil surfaces will move simultaneously to the well perforation. This event, if occurs in a well, will affect the well produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Controlling water coning in fractured reservoirs is more challenging than the homogeneous reservoirs because of the rapid movement of water through the fractures (Reda 2016). To counter the problem, Dabiri et al (2017) suggested the benefits of horizontal wells over vertical wells, showing (through simulation) that critical oil production rate in horizontal wells is greater than that of vertical wells in fractured formations. However, the problems may be further aggravated due to faulty well trajectory or strong acid treatment, resulting in rapid deterioration of well performance.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling water coning in fractured reservoirs is more challenging than the homogeneous reservoirs because of the rapid movement of water through the fractures (Reda 2016). To counter the problem, Dabiri et al (2017) suggested the benefits of horizontal wells over vertical wells, showing (through simulation) that critical oil production rate in horizontal wells is greater than that of vertical wells in fractured formations. However, the problems may be further aggravated due to faulty well trajectory or strong acid treatment, resulting in rapid deterioration of well performance.…”
Section: Introductionmentioning
confidence: 99%
“…Another parameter in relation to the fracture network that has been appraised and has an impact on the water intrusion corresponds to the well trajectory. Different studies concluded that horizontal wells are less susceptible to water intrusion than vertical wells, and thereby, water breakthrough may be delayed in fractured formations [8,12,13]. However, this concept might be subject to further analysis to avoid fracture data sampling bias from the fracture network.…”
Section: Introductionmentioning
confidence: 99%